Wear resistance of thermal spray WC-Co-VC nanostructured coatings - Cabral Miramontes, José Ángel; Gaona Tiburcio, Citlalli; Velasco Tellez, Abraham; Poblano Salas, Carlos; Almeraya Calderón, Facundo (InTech, 2016)
Thermally sprayed WC-Co-VC coatings are widely used based on their resistance to abrasive wear. This chapter shows the fabrication procedure of bimodal WC-Co-VC coatings applied by a high-velocity oxy-fuel (HVOF) thermal spray process. We analyzed the effects of the mixture content of the nanostructure and microstructure phase on the mechanical properties and wear resistance of the coating. Additionally, VC was added to the bimodal mixture and it presented the best characteristics. The combination of VC additions and a bimodal WC particle size distribution in the WC-Co coatings proved successful in increasing their mechanical properties, which permitted the coatings processed in this work to show better mechanical properties than those reported in the literature for coatings having exclusively a bimodal WC particles size distribution or those only doped with VC additions. The effects of nanostructured phase contents on the microstructure and wear resistance of the coating are included.